Application of molecular genotyping to determine prevalence of HPV strains in Pap smears of Kazakhstan women. (January 2017) - Niyazmetova, Luiza; Aimagambetova, Gulzhanat; Stambekova, Nazigul; Abugalieva, Zaurech; Seksembayeva, Korlukain; Ali, Syed; Azizan, Azliyati
Abstract: Objectives: Human papillomavirus is the main causative agent for cervical cancer. However, few data are available about HPV prevalence in Kazakhstan. The aims of this study were to genotype HPV DNA in Pap smear samples of women to determine prevalence of carcinogenic HPV types in Astana, Kazakhstan and to analyze the association between HPV positivity and the cytology results of patient samples. Methods: Pap smear materials were obtained from 140 patients aged 18-59, who visited the outpatient gynecological clinic. Microscopic examination was done to detect dysplasia, and HPV genotyping was done using real-time multiplex PCR. Results: HPV testing showed that among 61 HPV positive patients, the most prevalent types were 16 and 18. Microscopic examination showed that 79% of the samples had normal cytology, while 13% had CIN grade I, 5% had CIN grade II, and 3% had CIN grade III. The analysis revealed that 12% of the samples had CIN cytology and presence of HPV. Approximately 31% had HPV without cervical dysplasia, while 8% of samples were CIN positive without HPV infection. A statistically significant relationship between HPV 16 and HPV 33 positive samples and CIN grade II and III was found. Conclusions: Overall, this study will help to strengthen and guide health policy implementation of primary and secondary cervical cancer prevention strategies in Kazakhstan.